Bob

]]>For a lot of people, a proof is something that has human value. An arbitrary calculation is not a proof.

]]>Nice 'proof'. When applying a square root you have to remember that two roots are possible.

9 =9 but 3 ≠ -3

To check out any algebra just substitute some numbers to see what is happening.

I chose a = 5; b = 3 and so c = 8.

Here is your 'proof' with those numbers.

8 x 2 = 8 x 2

25 - 9 = 40 - 24

25 - 40 = 9 - 24

25 -40 + 32 = 9 - 24 + 32

(5-4)^2 = (3-4)^2

All so far is correct. But then we have the square root.

(5-4) ≠ (3-4)

But, back to the algebra, if we take a negative root:

a - c/2 = -b + c/2

a + b = c/2 + c/2 = c

Now it's correct but hasn't given anything new.

Bob

]]>Let us number the steps:

From (5) to (6), there is a fallacy.

The the step (5) does not necessarily equal (6).

Got it?

What went wrong?

]]>